2009
DOI: 10.1007/s00125-009-1554-x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium, vitamin D and dairy intake in relation to type 2 diabetes risk in a Japanese cohort

Abstract: Aims/hypothesis Calcium and vitamin D have been implicated in the development of type 2 diabetes, but epidemiological evidence is limited. We examined prospectively the relation of calcium and vitamin D intake to type 2 diabetes risk in a Japanese cohort. Methods Participants were 59,796 middle-aged and older men and women, who participated in the Japan Public Health Center-based Prospective Study and had no history of type 2 diabetes or other serious diseases. Dietary intake of calcium and vitamin D were esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
109
4
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(132 citation statements)
references
References 33 publications
10
109
4
3
Order By: Relevance
“…A total of seven publications with cohort studies (Choi et al, 2005;Liu et al, 2006;Pittas et al, 2006;van Dam et al, 2006;Elwood et al, 2007;Kirii et al, 2009;Villegas et al, 2009) on dairy and milk consumption and T2DM were included according to the criteria (Table 1). In the study by Kirii et al (2009), participants were divided to men and women for observation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of seven publications with cohort studies (Choi et al, 2005;Liu et al, 2006;Pittas et al, 2006;van Dam et al, 2006;Elwood et al, 2007;Kirii et al, 2009;Villegas et al, 2009) on dairy and milk consumption and T2DM were included according to the criteria (Table 1). In the study by Kirii et al (2009), participants were divided to men and women for observation.…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Kirii et al (2009), participants were divided to men and women for observation. Thus, it was considered two studies when the observed items were combined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of cases ranged from 199 to 4843, and the cohort sizes ranged from 5200 to 83 779. Four studies included women only, whereas two studies enrolled both men and women, of which one 5 reported separate results by sex. The length of follow-up ranged from 5 to 20 years.…”
Section: Resultsmentioning
confidence: 99%
“…A cohort study in The Netherlands found an odds ratio of 0.28 (95% CI, 0.10-0.81) for >75 nmol l −1 versus <25 nmol l −1 (males) but no effect for females [453]. A cohort study in Japan found an odds ratio of 0.62 (95% CI, 0.41-0.94) for males and 0.59 (95% CI, 0.38-0.91) for females for highest versus lowest calcium intake with higher vitamin D intake [454].…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 98%